Pengaruh Manajemen Laba Sebelum Initial Public Offering (IPO) terhadap Kinerja Keuangan Perusahaan (Studi pada Perusahaan Sektor Properti, Real Estate, dan Konstruksi Bangunan Melakukan IPO Tahun 2018-2021 yang Terdaftar di Bursa Efek Indonesia) - Sihaloho, Maria Petra Angelina Br.; Gaol, Manatap Berliana Lumban; Harefa, Meilinda Stefani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of the accrual earnings management before IPO and the real earnings management before IPO on the company's financial performance after the IPO. This study uses secondary data with the object of research on property, real estate and building construction sector companies conducting IPOs in 2018-2021 which are listed on the Indonesia Stock Exchange. There are 32 companies that the became research sample using purposive sampling method. The technique of data analysis in this study is the Multiple Regression Analysis with using SPSS 26 software. The results of data testing conducted in this study indicate that accrual earnings management before IPO has a negative and significant effect on financial performance, while real earnings management before IPO has no significant effect on financial performance.